The Role of Ca2 + in Maturation and Reprogramming of Bovine Oocytes: A System Study of Low-Calcium Model - Meng, Lin; Hu, Hongmei; Liu, Zhiqiang; Zhang, Luyao; Zhuan, Qingrui; Li, Xue; Fu, Xiangwei; Zhu, Shien; Hou, Yunpeng (Frontiers in Cell and Developmental Biology, 2021)
[Ca2+]i is essential for mammalian oocyte maturation and early embryonic development, as those processes are Ca2+ dependent. In the present study, we investigated the effect of [Ca2+]i on in vitro maturation and reprogramming of oocytes in a lower calcium model of oocyte at metaphase II (MII) stage, which was established by adding cell-permeant Ca2+ chelator BAPTA-AM to the maturation medium. Results showed that the extrusion of the first polar body (PB1) was delayed, and oocyte cytoplasmic maturation, including mitochondrial and endoplasmic reticulum distribution, was impaired in lower calcium model. The low-calcium-model oocytes presented a poor developmental phenotype of somatic cell nuclear transfer (SCNT) embryos at the beginning of activation of zygotic genome. At the same time, oxidative stress and apoptosis were observed in the low-calcium-model oocytes; subsequently, an RNA-seq analysis of the lower-calcium-model oocytes screened 24 genes responsible for the poor oocyte reprogramming, and six genes (ID1, SOX2, DPPA3, ASF1A, MSL3, and KDM6B) were identified by quantitative PCR. Analyzing the expression of these genes is helpful to elucidate the mechanisms of [Ca2+]i regulating oocyte reprogramming. The most significant difference gene in this enriched item was ID1. Our results showed that the low calcium might give rise to oxidative stress and apoptosis, resulting in impaired maturation of bovine oocytes and possibly affecting subsequent reprogramming ability through the reduction of ID1.